2013
DOI: 10.1002/lt.23597
|View full text |Cite
|
Sign up to set email alerts
|

Complete tumor encapsulation on magnetic resonance imaging: A potentially useful imaging biomarker for better survival in solitary large hepatocellular carcinoma

Abstract: The aim of this study was to determine the prognostic value of complete tumor encapsulation as visualized on magnetic resonance imaging (MRI) in patients with a solitary large hepatocellular carcinoma (HCC) beyond the Milan criteria for liver transplantation (LT). Between December 2000 and March 2011, 57 patients who had a solitary HCC exceeding 5 cm in diameter at the time of initial MRI before any treatment were identified. MRI images of the patients were independently reviewed by 2 experienced readers for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…A lack of tumour encapsulation is another risk factor. It was shown in a recent study that complete tumour encapsulation predicted better OS, a better response to downstaging therapy and eventual liver transplantation . Last but not least, macrovascular invasion to the main portal vein or its branches was seen in 9 of the 37 patients.…”
Section: Discussionmentioning
confidence: 93%
“…A lack of tumour encapsulation is another risk factor. It was shown in a recent study that complete tumour encapsulation predicted better OS, a better response to downstaging therapy and eventual liver transplantation . Last but not least, macrovascular invasion to the main portal vein or its branches was seen in 9 of the 37 patients.…”
Section: Discussionmentioning
confidence: 93%
“…Of the 12 patients, 6 had digitized radiographic imaging available for review, compared with the detailed radiographic reports available for the remaining 6 patients. Of 7 lesions in these 6 patients, all demonstrated infiltrative margins and none were encapsulated . A heterogeneous or mosaic pattern of enhancement was noted in 6/7 lesions (85.7%) with 3/7 (42.9%) lesions meeting OPTN 5 criteria, thus resulting in the mistaken diagnosis of HCC by imaging criteria alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using MRI, one report showed that patients with fat-containing HCC had less tumor progression, less distant metastases, and a longer time to tumor progression when compared to patients with non-fat containing HCC [16] . Another report showed that patients with complete tumor encapsulation on MRI had lower AFP levels, an absence of vascular invasion, more patients in Child-Pugh class A, and significantly longer survivals [17] . Further, the authors also noted that the rates of downstaging and eventual liver transplantation were significantly higher.…”
Section: Discussionmentioning
confidence: 99%